Agricultural factor markets and India's small farmers - Bezbaruah, Madhurjya Prasad; Das, Anup Kumar (ed); Goswami, Binoy (ed); Das, Anup Kumar (Los Angeles SAGE Publications, 2022)
Groundwater Markets : Functioning and Issues